La Responsabilidad del Revisor Fiscal en el caso Odebrecht; Ruta del Sol II (2022)
In recent years there have been scandals regarding corruption of civil works in Colombia. One of them is the one in which one of the most important construction companies in the field was involved, such as the construction company Norberto Odebrecht de Colombia SAS; who was in charge of carrying out multimillion-dollar contracts with the help of its partners, state control regulatory entities as reported (Justice, 2001-2016) and professionals who lent their name and signature as public accountants among others; violating the code of professional ethics for accounting (IFAC, 1977) that is regulated in Decree 0302 of February 20, 2015 and in the Professional Code of Ethics found in Law 43 of 1990 that tells us about " A set of norms and values aimed at regulating the behavior ofpeople within the context and environment of a workplace, proposing regulations that mustbe compulsorily complied with by the members of the workplace”.